The Guardian of Family Right (Telaah Putusan Mahkamah Konstitusi Berkenaan dengan Hak-Hak Keluarga) - Syaifullahil Maslul (Program Studi Ilmu Hukum Universitas Maritim Raja Ali Haji, 2022)
The Constitutional Court is the Guardian of Family Rights. This is reflected in decisions relating to family rights. This study examined four decisions, 46/PUU-VIII/2010, 69/PUU-XIII/2015, 13/PUU-XV/2017, and 22/PUU-XV/2017. This study describes and examines the decisions of the Constitutional Court in relation to family rights. In addition, this study also aims to analyze the role of the Constitutional Court as the Guardian of Family Rights. This research is classified as library research with a conceptual approach. The results of this study, the Constitutional Court is the Guardian of Family Rights. The Constitutional Court stood on the judicial activism paradigm in the udicial review of family rights. Second, the Constitutional Court guarantees the fulfillment of family rights through its decision. Third, the Constitutional Court guarantees and improves family conditions through its decisions. This is because the family is the basic foundation of the nation and state. It is through the family that real human development is carried out.